Dystocia due to lateral deviation of head and carpal flexion in mare - a case report - G, Aswini Sivan; kujur, Anju; Kumar, Brijesh; Srivastava, Neeraj; Sahu, Tarun (Animal Reproduction Update, 2022)
Although dystocia in mares is uncommon, it may be brought on by the way the fetal extremities develop. Dystocia in horses is a serious condition. The referral veterinary polyclinic of ICAR-IVRI received a call about a stray mare who had been straining for the last four hours. She was about 6-7 years old. The absence of foetal responses revealed a dead foetus, and rectal examination indicated that it to be a case of lateral deviation of the head. For the purpose of facilitating head-deviation correction, the foetus was repulsed back into the uterus. A forcible extraction was used to remove the dead foetus following the use of the obstetrical hook to adjust the fetal head position. Anti-inflammatory drugs along with antibiotics were administered. Additionally, tetanus shots were administered prophylactically. The most frequent cause of dystocia in mare is head deviation, which is a critical condition that can affect both the dam and the foetus